Mesenchymal stromal cell exosomes for drug delivery of prostate cancer treatments: a review - Chengran Wang; Yanshuo Feng; Xinao Rong; Jingguo Yan; Baisong Lv; Hongyu Jiang; Lian Duan; Jinlan Jiang (Stem Cell Research & Therapy)
Abstract Interest in prostate cancer as a research topic has gradually increased. As a result, a series of innovative treatment strategies have emerged with an in-depth understanding of the disease. Owing to their unique biological characteristics, mesenchymal stromal cell exosomes (MSC-Exos) have garnered significant attention for their potential to deliver targeted drugs and enable precise prostate cancer treatment. Herein, prostate cancer treatment with MSC-Exos drug-delivery systems is reviewed. This review provides a comprehensive introduction to the advantages of these systems, current research trends and progress, as well as an analysis of current challenges and future research directions. Moreover, this review lays a solid foundation for the continued development and application of MSC-Exos. Graphical abstract